LEGAL REMEDIES OF THE INVESTMENT ALERT TASK FORCE IN COUNTERING FICTITIOUS INVESTMENTS - Maryano (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The purpose of this study is to examine how to protect investors from illegal investment crimes. So that the public can be educated. This research uses a normative juridical approach method. The result is that the mode of fraud under the guise of illegal investment still occurs frequently, although with the formation of the Investigation Alert Task Force the fraud still occurs although it is not as lively as it used to be. Especially after the emergence of cases of artists who were caught for illegal investments. The resilience of Indonesia's economic conditions, especially when hit by the pandemic but still quite strong, is still quite strong, especially positive growth is still occurring in this country. Practically this is the goal of investors. Plus based on the data, the new middle class continues to crawl up. Apparently, this has contributed to increasing the occurrence of crime in the investment sector. Investment is very important for the economic development of a country. A country will find it difficult to develop if there is no investment to support its process. Investment can also be called investing money or capital, which aims to get a profit. An investment is the obligation to inject funds in an asset for a certain period of time in the future. Crime in the investment sector gives rise to fictitious investments that are widely offered to the public by illegal investment companies. People who actively invest are sometimes less vigilant and clear in making investment choices. The rampant incidence of fraud under the guise of illegal investment has made the state present, one of which is the establishment of the Investment Alert Task Force. Through library research and normative descriptive qualitative methods, the author wants to dive into the extent to which the task force commanded by the FSA will become a stronghold for investors.